2011
DOI: 10.1080/00224490903556374
|View full text |Cite
|
Sign up to set email alerts
|

Visual Attention to Erotic Images in Women Reporting Pain with Intercourse

Abstract: The coupling of sex and pain creates an interesting theoretical conundrum of clinical significance: Are women with dyspareunia distracted from sexual stimuli, or are they hypervigilant to sexual stimuli because these stimuli elicit thoughts and expectations of pain? This study measured attention to sexual stimuli in women reporting persistent pain with intercourse, women reporting low sexual desire, and women reporting no sexual problems. Participants viewed a series of erotic images, each containing an object… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
28
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 58 publications
(65 reference statements)
0
28
0
Order By: Relevance
“…Moreover, a more negative BI during sexual activities was associated with higher pain intensity during intercourse. Women with PVD tend to be hypervigilant about their pain [70] and to focus their attention on nonerotic stimuli [71]. In the present study, women with PVD1 reported more anxiety regarding their body during sexual activities compared with no‐pain controls.…”
Section: Discussionmentioning
confidence: 41%
“…Moreover, a more negative BI during sexual activities was associated with higher pain intensity during intercourse. Women with PVD tend to be hypervigilant about their pain [70] and to focus their attention on nonerotic stimuli [71]. In the present study, women with PVD1 reported more anxiety regarding their body during sexual activities compared with no‐pain controls.…”
Section: Discussionmentioning
confidence: 41%
“…It is possible that when one or both partners of these couples have relatively high AEE, they will feel more conflicted over expressing these emotional preoccupations and, in turn, also more anxious and less able to refocus on the sexual activity at hand—thereby negatively impacting the sexual function of the couple as a whole [54]. This is in accord with the cognitive distraction model of sexual dysfunction [55], which has been found to be relevant to women who suffer from painful intercourse [56]. In an eye‐tracking visual attention study, women with dyspareunia were found to spend less time focusing on erotic aspects of images than a control group of women.…”
Section: Discussionmentioning
confidence: 99%
“…Also, those who are more sexually excitable miss more target stimuli in Go/No-Go tasks (Macapagal, Janssen, Fridberg, Finn, & Heiman, 2011). Finally, women with lower sexual desire fixate more on contextual than sexual parts of erotic scenes than controls (Lykins, Meana, & Minimi, 2011). These attentional effects affected by sexual desire level also are malleable within-person to exogenous testosterone (Van der Made et al, 2009).…”
mentioning
confidence: 99%